UKMenCar4: A cross-sectional survey of asymptomatic meningococcal carriage amongst UK adolescents at a period of low invasive meningococcal disease incidence. - Bratcher,HB; Rodrigues,CMC; Finn,A; Wootton,M; Cameron,JC; Smith,A; Heath,P; Ladhani,S; Snape,MD; Pollard,AJ; Cunningham,R; Borrow,R; et al. (Wellcome Open Res, 2019)
Carriage of Neisseria meningitidis, the meningococcus, is a prerequisite for invasive meningococcal disease (IMD), a potentially devastating infection that disproportionately afflicts infants and children. Humans are the sole known reservoir for the meningococcus, and it is carried asymptomatically in the nasopharynx of ~10% of the population. Rates of carriage are dependent on age of the host and social and behavioural factors. In the UK, meningococcal carriage has been studied through large, multi-centre carriage surveys of adolescents in 1999, 2000, and 2001, demonstrating carriage can be affected by immunisation with the capsular group C meningococcal conjugate vaccine, inducing population immunity against carriage. Fifteen years after these surveys were carried out, invasive meningococcal disease incidence had declined from a peak in 1999.  The UKMenCar4 study was conducted in 2014/15 to investigate rates of carriage amongst the adolescent population during a period of low disease incidence. The protocols and methodology used to perform UKMenCar4, a large carriage survey, are described here.